2021
DOI: 10.1097/pai.0000000000000997
|View full text |Cite
|
Sign up to set email alerts
|

IDH1/2 Mutations in Patients With Diffuse Gliomas: A Single Centre Retrospective Massively Parallel Sequencing Analysis

Abstract: Patients below 55 years were genetically studied because the prevalence of isocitrate dehydrogenase 1 (IDH1) decreases in older patients and on grounds of cost-effectiveness, as suggested by the World Health Organization (WHO) in 2016. The aim of our study was to use novel massively parallel sequencing (MPS) approaches to examine rare variants of IDH1/2 in Czech diffuse astrocytic and oligodendroglial tumors (gliomas) patients below 55 years of age who had been immunohistochemically (IHC) diagnosed as IDH1 R13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…This research also compared the similarities between IDH1 and TTC7B expressions. As indicated by WHO, IDH1 phenotypes serve as a unique diagnostic technique for clinical usage and categorization of diffuse gliomas among adults is mostly determined by IDH1 mutation status [ 3 , 24 , 25 ]. In this study, we investigated the differences between IDH1 wild type and IDH1 -R132 mutant groups.…”
Section: Discussionmentioning
confidence: 99%
“…This research also compared the similarities between IDH1 and TTC7B expressions. As indicated by WHO, IDH1 phenotypes serve as a unique diagnostic technique for clinical usage and categorization of diffuse gliomas among adults is mostly determined by IDH1 mutation status [ 3 , 24 , 25 ]. In this study, we investigated the differences between IDH1 wild type and IDH1 -R132 mutant groups.…”
Section: Discussionmentioning
confidence: 99%
“…In diffuse astrocytomas, the percentage of IDH1 mutations was 76.7%, while in glioblastoma, this percentage was 5.6% [14]. Furthermore, a more recent study that included astrocytic and oligodendroglial tumors proved the presence of IDH1 mutations in 60% of diffuse astrocytomas, 33% of anaplastic astrocytomas, 67% of anaplastic oligodendrogliomas, and 5% of glioblastomas [15]. An earlier meta-analysis analyzing IDH1 and IDH2 mutations from 55 different studies with 9487 glial tumors showed that both mutations were independently and statistically significantly associated with better overall survival and progression of free survival and disease-free survival in glioma patients [16].…”
Section: Discussionmentioning
confidence: 98%
“…Isocitrate dehydrogenase (IDH) mutation and O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation status were assessed using standard techniques employed at the three neuro-oncology centers described in detail in previous reports [19][20][21]. Briefly, immunohistochemistry (anti-IDH1R132H) and genotyping with Next-Generation Sequencing (Nextera XT kit, Illumina, San Diego, CA, USA) were employed for IDH mutation analyses and real-time methylation-specific PCRs or pyrosequencing analysis of MGMT promoter methylation.…”
Section: Investigation Of Idh Mutation and Mgmt Promotor Methylationmentioning
confidence: 99%